Service Quality on Customer Loyalty: Mediation of Customer Satisfaction - Hidayat, Muhammad Anhar; Rasyid, Abdul; Pasolo, Fahruddin (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study investigates the impact of Service Quality on Customer Satisfaction and Loyalty in the e-commerce sector, emphasizing the mediating role of Customer Satisfaction. The research hypothesizes that improvements in Service Quality positively affect both Customer Satisfaction and Loyalty and that Customer Satisfaction mediates the relationship between Service Quality and Customer Loyalty. Research Design and Methodology: A quantitative research design was employed using Structural Equation Modeling (SEM) to examine the relationships among Service Quality, Customer Satisfaction, and Customer Loyalty. The sample consisted of 120 customers from CV Cipta Buana Irian, a printing company in the e-commerce sector, selected through accidental sampling. Data were collected via questionnaires and analyzed to test the proposed hypotheses, ensuring validity and reliability through statistical tests. Findings and Discussion: The results demonstrate that Service Quality significantly influences Customer Satisfaction and Loyalty. Moreover, Customer Satisfaction mediates the effect of Service Quality on Customer Loyalty, indicating that high Service Quality enhances Customer Satisfaction, which boosts Customer Loyalty. These findings align with previous research, highlighting the importance of Service Quality and Customer Satisfaction in fostering Customer Loyalty in e-commerce settings. Implications: The findings suggest practical and theoretical implications for e-commerce businesses focused on improving customer satisfaction and loyalty. Future research should explore diverse sectors and methodologies, such as longitudinal studies, to understand these dynamics better and consider the role of digital engagement strategies in e-commerce.